Effect of structural promoters on calcium based sorbents from waste derived sources. (September 2020) - Nawar, Azra; Ali, Majid; Mahmood, Mariam; Anwar, Mustafa; Khan, Zeeshan Ali
Graphical abstract: Highlights: Waste marbledust and eggshell were used as cheap source of CaO. Sol gel combustion achieved the highest performance. Wet method was the feasible, cost effective, environmental friendly method. Al doped achieved the higher conversion and stability. Abstract: Calcium looping process is an important technology for high temperature CO2 scrubbing. Calcium based sorbent decays rapidly after cyclic reactions, hence enhanced cyclic stability of the sorbent should be developed. We studied three different refractories including Al, Mg and La based supports which were synthesized using the dry mixing, wet-mixing method and Sol Gel Combustion Synthesis (SGCS) methods, through which the dopants are completely mixed into CaO/CaCO3 particles. The sorbents were characterized by SEM/EDS and XRD. The carbonation conversion and cyclic stability of sorbents were tested by Thermo-Gravimetric Analyser (TGA) under similar conditions. TGA results demonstrated that marble-dust doped sorbents are able to achieve higher conversion than eggshell sorbents. Hence, further analysis was focused on marble-dust sorbents. SGCS exhibit much superior cyclic performance as compared to wet and dry method, however, wet method is effective due to the low cost less time consumption and scale up issues. This analysis demonstrated that marble-dust sorbents doped with Al i.e CaO:Al (90:10) maintained the best conversion (91 %) and stability over 20 reaction cycles in comparison with dopant ratio CaO: Al (80:20) i.e., 73 %. Similarly, Mg and La dopants showed best conversion and cyclic strength at the doping ratio of 90:10. Hence, conversion rate and cyclic stability is maximum for all the dopants Al, Mg and La with dopant ratio of 90:10 in comparison with ratios 80:20 and 70:30. Furthermore, among all the dopants, Al dopant gives highest conversion rate and cyclic stability.